Colonial Oppression and Indigenous Response: A Postcolonial Study of Ngũgĩ wa Thiong’o’s Novel, Weep Not, Child through Fanon’s Lens - Mehran Ullah khan; Hina Gul; Tahir Shah; Tariq Hussain; Lubaba Noor (Social Science Review Archives, 2025)
This research analyzes Ngugi Wa Thiong`o’s Weep Not, Child in the perspective of Post Colonialism. The study specifically aims at investigating racial discrimination, violence and persecution, and colonial exploitation in the backdrop of Kenyan colonial history. The qualitative mode of research and textual analysis is used as research method. Frantz Fanon’s views were applied as theoretical framework for the analysis of the study. Furthermore, Fanon views specifically related to racism, violence and colonial exploitation from Wretched of the Earth was taken as research design. In the light of thorough analysis research results reveal that Colonialism is a fierce and ruthless demonstration of controlling the colonized masses and territories through violence and assault. The colonizers entry into the colonized territory of Kenya is illegal and based on malignity. Apparently, they come up with the slogan to educate and civilized the Kenyan people. But in reality, they had their political agenda with them to make the people slaves so that to plunder their resources and wealth, subjugate their lands and to establish their own government to impose their policies upon them. On the other hand, Kenyan people in course of time realized that this brutal mentality and attitude ought to be responded through counter violence only. Finally, this research study is highly significant for other future researchers as it provide them insight and paves the way for them to look at issues of power, economics, politics, religion, and culture and how these elements work in relation to colonial hegemony, Neo – Colonialism, Colonial imperialism etc.